Numerical Investigation of the Transient Heat Transfer of a Blood Shipping Box - Celik, Nevin; Bayazit, Yilmaz (Springer/Plenum Publishers, 2011)
In this study, the design of a blood reservoir is implemented by numerical simulation of the transient heat transfer in the reservoir. The blood is considered to be kept at constant temperature in a flat, multi-compartment cylindrical reservoir under hot air temperature. A commercial phase-change media (PCM) (CaCl2 center dot 6H(2)O) and insulation materials are employed to keep the blood at a constant temperature. The parametric values in this study are the type and thickness of the insulation material and the thickness of the PCM layer. Two types of low-density insulation material are analyzed (extruded polystyrene and glass fiber). The thickness of the extruded polystyrene ranged from 0.25 cm to 1 cm, and the thickness of the PCM layer was varied from 1.5 cm to 2.5 cm.
Keywords: Blood reservoir; Shipping box; Transient heat transfer